Analisis Perilaku Material dan Komposisi Engineered Cementitious Composite : Review Studi - Indra Komara; Priyo Suprobo; Faimun Faimun; Data Iranata (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2022)
Engineered Cementitious Composite (ECC) concrete or micromechanical modeled concrete using analysis of a mixture of fiber and other added materials can produce a tensile strain capacity of up to three hundred to five hundred times compared to the strain capacity of conventional concrete. A review related to several studies that have been carried out previously on the properties of ECC and their constituent materials is presented in this paper. The behavior of the material is reviewed as an investigation parameter followed by determining the composition of the mixture, namely the effect of the water-cement ratio, the shape and length of the fiber and the addition of additives. The fiber volume fraction review was limited to between 2% to 3%, which resulted in outstanding tensile strain behavior. As it is known, ECC has an excellent capacity in terms of strain behavior which is accompanied by a large number of mico cracking patterns. ECC crack widths are usually predominantly less than 100 μm. ECC behavior is closer to that of steel which can bend or be ductile, whereas conventional concrete is brittle.